A frame analysis of the coverage of Islam/Muslims and terrorism in Time and The Economist - Yusoff, Sofia Hayati (2014)
In portraying Islam especially after the September 11 attacks, a number of studies found that terrorism has been repeatedly associated with Islam/Muslims by most of international media. There is a perception that international media play a vital role in creating a relationship between Islam/Muslims and terrorism in their coverage that leads to the formation of frames on Islam/Muslims and terrorism. Based on this view, the researcher has conducted a content analysis of two international news magazines, Time and The Economist, aimed at examining the coverage of the selected articles in terms of sources of news, themes, and comparison among four different periods of sampling; a one year period right before September 11, a one year period right after September 11, a one year period after five years of September 11 and a one year period after ten years of September 11. The researcher also looked at the analysis of the news stories by qualitatively extracting the frames that were formed pertaining to Islam/Muslims and terrorism in all articles selected. This study has applied content analysis as the research methodology in collecting, coding and analyzing the data. In this study, the researcher used three main key variables in understanding the analysis of the frames. The three variables were the themes, the overall framing of Islam/Muslims with terrorism and the use of frames by these news magazines. All paragraphs pertaining to the issue during the study periods were analyzed. A total of 4,443 paragraphs were analyzed to determine the significant themes, overall framing and frames formation. For themes, the researcher has found that among most significant themes used by these Time and The Economist in covering stories related to Islam/Muslims are “conflict”, “politics” and violence/terrorism” while the analysis on overall framing showed that Islam/Muslims have been highly associated with terrorism in two out of four periods of sampling selected; a one year period right after September 11 and a one year period after five years of September 11. The researcher has finally discovered ten frames that have been consistently used by the Time and The Economist on Islam/Muslims in relation to terrorism issues throughout the four periods being studied; there are one year right before September 11, one year right after September 11, one year after five years of September 11, and finally one year after ten years of September 11.